2003
DOI: 10.1046/j.1525-1497.2003.20115.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving physicians’ knowledge of the costs of common medications and willingness to consider costs when prescribing

Abstract: Our brief educational intervention led to modest improvements in physicians' knowledge of medication costs and their willingness to consider costs when prescribing. Future research could incorporate more high-intensity strategies, such as outreach visits, and target specific prescribing behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(39 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…Given the demonstration by Korn and co-workers 16 of the benefits of improving the awareness of practitioners of the impact of patient expenses on prescribing patterns in a medical context, we trust that the cost-per-wear analysis reported here will be of similar benefit to contact lens practitioners and lens wearers.…”
supporting
confidence: 53%
“…Given the demonstration by Korn and co-workers 16 of the benefits of improving the awareness of practitioners of the impact of patient expenses on prescribing patterns in a medical context, we trust that the cost-per-wear analysis reported here will be of similar benefit to contact lens practitioners and lens wearers.…”
supporting
confidence: 53%
“…There was no statistical significance in the implementation rate per class year (P = .26). including 9 teaching methods (eg, lectures, seminars, small group, role play, and workshops [19][20][21]; simulated case scenario [22]; morbidity or clinicopathologic conferences; grand rounds; orientation on community resources; video examples of role play [23]; review of resident "sign out"; hospital quality assurance programs or committees; and teamwork curriculum, exercises, and training [24,25]) and 12 evaluation methods (eg, cognitive testing [26], self-reflection and self-reporting, self-directed chart audit or postclinic or postdischarge analysis [27], portfolio documentation [28], surveys of residents [29], resident exit interview(s), low-and high-fidelity simulations [30], evaluation of case-based presentations, direct observation [30], simulations including teamwork exercises [25], standardized patients [23,31], and 360°global evaluation from system participants [32]). …”
Section: Discussionmentioning
confidence: 99%
“…If we acknowledge that physicians make choices which impact on how the total health-care resources are allocated between tasks and patients, and as such should be expected to choose cost effective treatments, they must be given the proper information and decision support tools. We see from other studies that physicians do not have good access to cost information, and often they believe that they could prescribe more cost effectively if they had access to better information [11,30,31]. In a recent study, Feldman, Shihab et al concluded that displaying the prices of diagnostic tests can influence physicians ordering behaviour and lead to a reduction in costs [32].…”
Section: Discussionmentioning
confidence: 99%